Post‐release dispersal and spawning movements of a translocated lake sturgeon (Acipenser fulvescens, Rafinesque 1817) population in the Mattagami River, Ontario. (5th February 2019) - Boothroyd, Maggie L. E.; Haxton, Tim J.; Hendry, Charles; Romain, Derrick A.; Wilson, Chris C.; Whillans, Tom
Summary: Species translocations are increasingly being used as a management tool to mitigate population losses due to such factors as habitat degradation and fragmentation, but post‐introduction follow‐up is relatively sparse. Post‐translocation telemetry can assess success by identifying activity, emigrations, survival, habitat usage, and reproductive events, aiding in the continued management of translocated populations and informing future efforts. This study assessed movement of translocated adult lake sturgeon ( Acipenser fulvescens ) immediately post‐release and a decade later, and tested for associations between environmental variables and spawning movements. Prior to their translocation in 2002, 13 of 51 adult lake sturgeon were surgically implanted with radio telemetry tags and tracked for 1 year. In 2011 and 2013, eight additional adults were captured within the reintroduction site and implanted with radio‐tags. Six of the 13 sturgeon tagged in 2002 dispersed downstream over a dam during the early post‐release period. In spring 2014, tagged adults were tracked to the spillway at the release area's inflow, and spawning was confirmed by larval captures. Movement data for tagged adults differed between the two tracking periods, showing marked differences in behaviour over time. Water velocity was correlated with upstream and downstream spawning movements, with water temperature also correlated with downstream movement. Research regarding post‐translocation movement and dispersal provides insight on behavioural responses following translocation, and may improve outcomes by informing future efforts.